2023
DOI: 10.3390/md21030174
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Marine Chemical Ecology Research on the Discovery and Development of New Pharmaceuticals

Abstract: Diverse ecologically important metabolites, such as allelochemicals, infochemicals and volatile organic chemicals, are involved in marine organismal interactions. Chemically mediated interactions between intra- and interspecific organisms can have a significant impact on community organization, population structure and ecosystem functioning. Advances in analytical techniques, microscopy and genomics are providing insights on the chemistry and functional roles of the metabolites involved in such interactions. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 220 publications
0
11
0
Order By: Relevance
“…Avila and Angulo-Preckler demonstrated that P. tunicata -produced marine bacteria have a competitive edge over their fungi counterparts in surface colonization. Additionally, P. tunicata -derived yellow chemical molecule, tamjamine, is believed to possess antibacterial properties ( Avila and Angulo-Preckler, 2020 ) that effectively suppress the growth of staphylococci and bacilli ( Tan, 2023 ).…”
Section: Biologically Active Marine Microorganismsmentioning
confidence: 99%
“…Avila and Angulo-Preckler demonstrated that P. tunicata -produced marine bacteria have a competitive edge over their fungi counterparts in surface colonization. Additionally, P. tunicata -derived yellow chemical molecule, tamjamine, is believed to possess antibacterial properties ( Avila and Angulo-Preckler, 2020 ) that effectively suppress the growth of staphylococci and bacilli ( Tan, 2023 ).…”
Section: Biologically Active Marine Microorganismsmentioning
confidence: 99%
“…Accordingly, screening campaigns revealed marine organisms as a particularly rich source of secondary metabolites with potential antimicrobial activity. Many marine organisms, such as sponges, corals, and algae, produce secondary metabolites as part of their defense against microbial pathogens in their environment necessary for organisms with a sessile lifestyle in a water environment [28,29]. Bioprospecting of the marine environment has gained much attention in recent years owing to its massive chemical and biological diversity [30].…”
Section: Marine Secondary Metabolites As a Sourcementioning
confidence: 99%
“…Marine organisms hold significant potential in becoming vital resources for the exploration of novel pharmaceuticals [ 1 , 2 , 3 ]. Notably, marine toxins, which mainly include toxic compounds of dinoflagellates, diatoms, and cyanobacteria by bivalve mollusks and other filter-feeding organisms such as algae in marine environments, stand out in this regard.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, marine toxins, which mainly include toxic compounds of dinoflagellates, diatoms, and cyanobacteria by bivalve mollusks and other filter-feeding organisms such as algae in marine environments, stand out in this regard. The chemical and biological diversity exhibited by marine toxins is vast, rendering them an exceptional reservoir for uncovering new medications [ 1 , 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%